Light-Weight Concrete Properties on Base Polymeric-Fiber-Waste Addition - Kh., Kuldashev; Sh., Jamolov (European Journal of Life Safety and Stability (2660-9630), 2022)
An analysis the effect of using fiber-waste materials as a fine aggregate a in a mixes are reported. Six different mixes were prepared and tested, which polymeric-fiber-waste was used as a sand from mass of quartz sand 15, 20 and 25%. in 6 consists. Investigated and test results showed, that incorporation fiber-waste into a mix increase flexural straight to 121% and 134%